Visualizing multimerization of plasticity-related gene 5 at the plasma membrane using FLIM-FRET - Köper, Franziska; Vonk, Danara; Dirksen, Malte W.; Gross, Isabel; Heep, Axel; Plösch, Torsten; Hipp, Mark S.; Bräuer, Anja U. (Frontiers in Molecular Biosciences, 2024)
Plasticity-related gene (PRG) 5 is a vertebrate specific membrane protein, that belongs to the family of lipid-phosphate phosphatases (LPPs). It is prominently expressed in neurons and is involved in cellular processes such as growth-cone guidance and spine formation. At a functional level, PRG5 induces filopodia in non-neuronal cell lines, as well as the formation of plasma membrane protrusions in primary cortical and hippocampal neurons. Overexpression of PRG5 in immature neurons leads to the induction of spine-like structures, and regulates spine density and morphology in mature neurons. Understanding spine formation is pivotal, as spine abnormalities are associated with numerous neurological disorders. Although the importance of PRG5 in neuronal function is evident, the precise mechanisms as to how exactly it induces membrane protrusions and orchestrates cellular processes remain unresolved. Here we used in vitro biochemical assays to demonstrate that in HEK293T cells a large fraction of PRG5 can be found in homo dimers and lager multimers. By using Fluorescence Lifetime Imaging (FLIM) to quantify Förster Resonance Energy Transfer (FRET), we were able to visualize and quantify the specific localization of PRG5 multimers in living HEK293T cells and in fixed immature primary hippocampal neurons. Here, we provide the first evidence that PRG5 multimers are specifically localized in non-neuronal filopodia, as well as in neuronal spine-like structures. Our findings indicate a potential functional role for PRG5 multimerization, which might be required for interaction with extracellular matrix molecules or for maintaining the stability of membrane protrusions.